Evaluation of the analgesic and antipyretic activity of methanol extract of Combretum bauchiense Hutch & Dalziel (Combretaceae) leaves - Odoh Uchenna Estella; Agubata Chuka William; Obi Patrick; Chikeoku Ikenna; Theodora Mba; Onugwu Obinna; Uzor Ginikachukwu (Elsevier, 2022)
Background: Medicinal plants make up a vital component of therapeutics. The pharmacologic effect of medicinal plants can be said to be related to the nature of their phytochemical constituents or secondary metabolites. Combretum bauchiense is an African folk plant of the family Combretaceae. Over the years Species of the Combretaceae family has been associated with native us as antipyretic and analgesic substances. Aim: This study aims to determine the phytochemical composition and evaluate the analgesic and anti-pyretic activity of the methanol extract of Combretum bauchiense (MECB) leaves. Materials and Methods: The phytochemical analysis and acute toxicity study of MECB was done using standard procedures. The analgesic and antipyretic activity of MECB was investigated using two models each, with Morphine (10 mg/kg) as the standard reference drug for analgesic activity and Paracetamol (150 mg/kg) for antipyretic activity. The analgesic activity of the extract was evaluated using formalin induced pain and tail flick analgesic method and the antipyretic activity was evaluated using baker's yeast and turpentine induced pyrexia. The study was investigated at doses of 100, 200 and 400 mg/kg body weight of the extract. Data was analyzed using One-way Anova followed by Tukey's Post-hoc test and P < 0.05 was considered significant. Results: The phytochemical analysis revealed the presence of flavonoids, alkaloids, saponins, tannins, proteins, carbohydrates, glycosides and reducing sugars. No acute toxicity symptoms observed on oral administration of MECB at 5000 mg/kg which indicates the safety of the extract. There was significant (P < 0.05) reduction in pain response of 71.43, 77.92, and 84.41% for 100, 200 and 400 mg/kg respectively for the formalin induced pain. For the tail flick test; 31.0, 56.05 and 48.31% increase in pain response time was observed at the doses of 100, 200 and 400 mg/kg respectively. MECB also showed antipyretic activity of 4.87 and 7.42% in Baker's yeast induced antipyretic model at the doses of 200 and 400 mg/kg respectively. While there was significant (P < 0.05) antipyretic activity; 2.28, 4.29 and 5.13% in the turpentine induced antipyretic model at the doses of 100, 200 and 400 mg/kg of extract respectively. Conclusion: The study shows that the Methanol extract of Combretum bauchiense leaves possesses both analgesic and antipyretic properties and justifies it's use in traditional medicine in the treatment of pain and fever. These results also indicated a possible inhibition of prostaglandin synthesis as the mechanism of antipyretic and analgesic activity of the extract.